Study protocol for efficacy and safety of steroid-containing mouthwash to prevent chemotherapy-induced stomatitis in women with breast cancer: a multicentre, open-label, randomised phase 2 study. Issue 2 (13th February 2020) - Kuba, Sayaka; Yamanouchi, Kosho; Matsumoto, Megumi; Maeda, Shigeto; Hatachi, Toshiko; Sakiko, Soutome; Kawashita, Yumiko; Morita, Michi; Sakimura, Chika; Inamasu, Eiko; Shibata, Kenichiro; Otsubo, Ryota; et al.
Abstract : Introduction: Stomatitis is a frequent adverse event in patients undergoing chemotherapy for breast cancer. Stomatitis can hamper oral nutrition resulting in malnutrition, reduce quality of life and introduce the need for dose reductions and interruption of chemotherapy; however, there is currently no standard approach for preventing chemotherapy-induced stomatitis. We aimed to assess the safety and efficacy of a dexamethasone-based elixir mouthwash for preventing chemotherapy-induced stomatitis in patients with early breast cancer. Methods and analysis: In this multicenter, randomised, controlled phase 2 trial, we will randomly assign 120 women with early breast cancer undergoing chemotherapy to use of a dexamethasone-based elixir or standard oral care, to compare their preventive effects on chemotherapy-induced stomatitis. Patients will be assigned in a 1:1 ratio. Patients in the intervention group will receive chemotherapy, oral care and a dexamethasone-based elixir (10 mL 0.1 mg/mL; swish for 2 min and spit, four times daily for 9 weeks), and patients in the control group will receive chemotherapy and oral care. The primary endpoint is the difference in incidence of stomatitis between the two groups. The sample size allows for the detection of a minimum difference of 20% in the incidence of stomatitis between the two groups. Secondary endpoints are severity of stomatitis, duration of stomatitis, completion rate of chemotherapy and adverse events. Ethics and dissemination: All participants signed a written consent form, and the study protocol has been reviewed and approved by the Clinical Research Review Board of Nagasaki University (CRB7180001). Trial registration number: UMIN Clinical Trials Registry (UMIN000030489).